Interprofessional education: A recognized necessity, a persistent challenge - Perspectives from a longitudinal study - Thales Guardia de Barros; Emerson Roberto dos Santos; João Daniel de Souza Menezes; Matheus Querino da Silva; Marco Antônio Ribeiro Filho; Fabio Argollo Ferreira; Lucas Antonio Moura Gonzalez; Aparecida Custódio Da Silva; Izabelle Pereira Trindade; Luana Mari Takahashi; Natalia Almeida de Arnaldo Silva Rodrigues Castro; Loiane Letícia dos Santos; et al. (PLoS ONE, 2025)
Background Interprofessional Education (IPE) is widely recognized as essential for fostering collaborative healthcare practices and improving patient outcomes. Despite its acknowledged importance, there remains a notable scarcity of longitudinal research assessing medical students’ readiness for IPE across distinct educational stages, particularly within diverse global contexts like Brazil. Aim This study sought to address this gap by longitudinally mapping and analyzing the evolution of medical students’ readiness for interprofessional learning throughout their academic training at a Brazilian university. Methods Employing a quantitative longitudinal design, 53 medical students from the 2021 cohort completed the validated Readiness for Interprofessional Learning Scale (RIPLS) at three critical time points: upon university entry (2021), at the conclusion of the basic science cycle (2022), and at the end of the clinical cycle (2024). Temporal changes were assessed using repeated measures analysis of variance (ANOVA). Results Significant global differences were observed over time in the “Teamwork and collaboration” and “Patient-centered care” dimensions. Specifically, “Patient-centered care” exhibited a non-linear pattern, characterized by an initial increase followed by a subsequent decrease. In contrast, the “Professional identity” dimension demonstrated remarkable stability across all measurement points. Conclusions These findings reveal the complex and dynamic nature of interprofessional readiness development during medical education. They strongly advocate for the early introduction of IPE, coupled with sustained and adaptive interventions throughout the entire educational continuum, particularly to address fluctuations in patient-centered attitudes and to foster an interprofessional identity from the outset. This study offers crucial empirical insights for optimizing IPE strategies and preparing future physicians for collaborative practice.